DETERMINAN YANG MEMPENGARUHI KEMISKINAN DI JAWA TIMUR TA 2022 (PENDEKATAN PENDAPATAN DAERAH) - Musyaffa, Muhammad Ashari; Agus Suman (Journal of Development Economic and Social Studies, 2024)
As a Province with the highest number of poor-population, East Java was also recognized as a top province in poverty alleviation in 2021 and 2022, Although there are still differences in the levels of poverty among various districts and cities. However, East Java was also ranked as the third province with the highest regional income and holds significant authority in optimizing its local resources, evident from the role of Regional Original Revenue (PAD) in total regional income. Examining regional income, there is no research involving Other Legitimate Revenue as one of the components in poverty alleviation. Therefore, this study aims to explore the role of regional income in poverty alleviation, specifically considering the optimization of fiscal decentralization authority and regional income. Additionally, the research investigates the role of relative poverty in addressing disparities in poverty levels. Utilizing a quantitative research approach with the One Least Square Data Cross Section method, the study indicates that Regional Original Revenue, Transfer Funds, and Overall Regional Income are determinants influencing poverty, while Other Legitimate Revenue does not play a significant role. The conditions of poverty disparity and its alleviation can be addressed through a focus on the quality of education and health as aspects of relative poverty.